Timely initiation of breastfeeding in Zimbabwe: evidence from the demographic and health surveys 1994–2015 - Yaya, Sanni; Bishwajit, Ghose; Shibre, Gebretsadik; Buh, Amos (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Timely initiation of breastfeeding or breastfeeding within 60 min of birth has been shown to be associated with significantly lower risk of infant mortality. The World Health Organization recommends starting breastfeeding within the first hour of birth, yet many women in sub-Saharan Africa do not observe this recommendation. To date, there is limited evidence of timely initiation of breastfeeding for Zimbabwe. Therefore, we undertook this study with the aim of calculating the trend in timely initiation of breastfeeding and to explore the correlates. Methods We used five rounds of Zimbabwe Demographic and Health Survey data conducted between 1999 and 2015. Participants were 15,923 mothers currently breastfeeding or who had a childbirth within five years preceding the surveys. Outcome variable was self-reported timing of timely breastfeeding for singleton births which was categorized as early (< 60 min), late (≥ 60 min to < 2 4 h) and very late (≥ 24 h). Results Prevalence of timely initiation of breastfeeding was 60.3% (95% Confidence Interval [CI] 57.44, 63.02) in 1999, 66.9% (95% CI 64.32, 69.4) in 2006, 65.8% (95% CI 63.7, 67.8) in 2011 and 58.3% (95% CI 56.3, 60.4) in 2015. It increased by 27 and 22% in 2006 and 2011 compared with that of the 1999 level respectively. We found no socio-economic and gender-based differentials in the prevalence of timely initiation of breastfeeding. Compared with women aged 15–19 years old, women 25–29 and 30–34 years old had higher odds of practicing timely initiation of breastfeeding. The odds of practicing timely initiation of breastfeeding among Muslim women (adjusted odds ratio [aOR] 1.2, 95% CI 1.07, 1.36) was 20% higher when compared with Christian mothers. Women who wanted to have their last child later (aOR 0.89, 95% CI 0.81, 0.97) had 11% lower odd of practicing timely initiation of breastfeeding when compared with women who wanted children then. Conclusions The prevalence of timely initiation of breastfeeding in Zimbabwe was 58.3% in 2015, well over the 50% target recommended by WHO for all countries to attain by 2025.